GENOTOXIC AND CARCINOGENIC STUDIES OF NORGESTREL IN DROSOPHILA MELANOGASTER - ABOU-EISHA, AHMED; El-din, Adel E (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to investigate, for the first time, the possible in vivo genotoxic and carcinogenic activity associated with exposure to norgestrel (NGT) drug through employing the very recently established and adjusted genotoxic and tumorigenic methods in Drosophila melanogaster. Methods: Two in vivo genotoxic test systems were used; one detects the somatic mutation and recombination effects (somatic mutation and recombination test [SMART] wing-spot test) and the other detects the primary DNA damage (the comet test) in the body cells of D. melanogaster. On the other hand, the warts (wts)-based SMART assay is a vital genetic examination in Drosophila used to identify and characterize cancer potential of compounds. Results: Four experimental doses of NGT were used (ranging from 0.24 Î¼M to 16 Î¼M). NGT was found to be non-genotoxic at all tested concentrations even at the highest dose level 16 Î¼M and failed to increase the frequency of tumors in the somatic cells of D. melanogaster. Conclusion: Our results strengthen the hypothesis that steroidal drugs might act through a non-genotoxic carcinogen mechanism where the carcinogenic properties occur by direct stimulation of cellular proliferation through a steroid receptor-mediated mechanism. In addition, the results obtained in this research work may contribute to highlighting the importance of NGT as a potent neuroprotective antioxidant drug.